Ordinances of the Mayor and Common Council of Jersey City, at 9, tit. 4, § 7 (1844) - (:unkn) unknown (General Publisher, 1844)
Prohibited the discahrge of any gun, pistol, cannon, fowling piece, or other fire-arms. Violators fined five dollars.
--
Keywords: DISCHARGE